2021
DOI: 10.1186/s12893-020-01015-z
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative hypotension is not associated with adverse short-term postoperative outcomes after esophagectomy in esophageal cancer patients

Abstract: Background The effect of low systolic blood pressure and its subsequent postoperative outcome during esophagectomy for esophageal cancer is not well studied. Methods A prospective study was conducted and data were collected on patients who underwent esophagectomy and esophagogastric anastomosis for esophageal cancer. Intraoperative hypotension (IOH), defined as systolic blood pressure (SBP) < 90 mm Hg lasting more than 5 min, was recorded. Patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…Zhu et al [ 44 ] reported that the clinical outcome was consistently poorer for the high metadherin expression group than for the low metadherin expression group in the cumulative recurrence rates and in the overall survival rates. Recent studies have shown that miR-497 is upregulated in several other types of cancer [ 4 ]. Lan et al [ 45 ] discovered that miR-497 over-expression protects tumor cells from apoptosis and enhances resistance to temozolomide in glioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al [ 44 ] reported that the clinical outcome was consistently poorer for the high metadherin expression group than for the low metadherin expression group in the cumulative recurrence rates and in the overall survival rates. Recent studies have shown that miR-497 is upregulated in several other types of cancer [ 4 ]. Lan et al [ 45 ] discovered that miR-497 over-expression protects tumor cells from apoptosis and enhances resistance to temozolomide in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the advancement of HCC diagnostic and therapeutic tools, the patients’ prognosis is still poor due to increased metastasis and recurrence rates. There is an essential need to discover new diagnostic and prognostic markers for better prediction of disease outcomes and improvement of patients’ survival [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, age, sex, and Tracheobronchial anatomy are intrinsic factors influencing this field. External factors such as residence, FB species, and prehospital time can be mentioned [ 6 ]. Cultural contexts and eating habits in specific geographic areas play a significant role [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most reports on learning curves or variability across practitioners for invasive treatments for neck or low back pain focus on interventions other than NRT, many of which lack high quality evidence supporting their efficacy and effectiveness. Moreover, they are based on small samples (e.g., ≤150 patients or ≤3 practitioners), do not use multi-level analyses to adjust results for patient prognosis as established by previously validated models, or have been conducted either retrospectively or outside routine practice conditions (e.g., based on data gathered in randomized controlled trials) [ 8 , 9 , 10 , 11 , 12 , 13 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Therefore, it is inappropriate to compare such data with results from this study.…”
Section: Discussionmentioning
confidence: 99%